La Revista de la Escuela Superior de Guerra "Tte Grl Luis María Campos" ; no. 587/2014 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (2014)
Ejemplar: Revista de la ESG. Año 92, no. 587 (mayo-ago. 2014). 163 p.